TEACHERS' LEADERSHIP STYLE AND STUDENTS' LEARNING MOTIVATION IN JUNIOR HIGH SCHOOLS - Wagiyo, Supiah; Nawanto, Condro (Edunomika Journal : Studies In Education And Development Economics, 2026)
Teachers' leadership style is a critical determinant of instructional effectiveness, particularly in English as a Foreign Language (EFL) contexts where student engagement is essential. This study aims to identify the dominant leadership styles applied by English teachers and to evaluate the level and characteristics of students' learning motivation in junior high schools on Bangka Island. Employing a quantitative survey design, data were collected from 20 English teachers and 20 seventh-grade students. The Leader Behavior Description Questionnaire (LBDQ) and a multi-dimensional motivation scale were utilized. Data analysis involved descriptive statistics and mapping into the Ohio State leadership quadrants. Findings reveal that teachers predominantly exhibit a "High Initiating Structure and High Consideration" style (Quadrant III), indicating an effective balance between task-oriented and relationship-oriented behaviors. Students' motivation was generally high, driven by strong internal factors such as sense of agency (84%) and need for action (76%). However, external support from "significant others" showed significant variability. The study suggests that teacher leadership is not a fixed trait but a situational capability to synchronize instructional structure with students' psychological needs, thereby fostering an optimal EFL learning environment.